2008
DOI: 10.1177/0022022107313902
|View full text |Cite
|
Sign up to set email alerts
|

Are Japanese More Collectivistic Than Americans?

Abstract: This study examines whether the common view that Japanese are more collectivistic than Americans is valid or not in three respects: First, the authors point out that those empirical studies that were directly related to the commonly accepted definition of individualism and collectivism (I/C) did not support the common view and that those studies whose relations to I/C were merely inferred were inappropriate in judging its validity. Second, the authors show that the reference-group effect (Heine, Lehman, Peng, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 32 publications
3
15
0
Order By: Relevance
“…A key focus has been the relationship of self-enhancement and self-effacement to selves contrasted in terms independence/interdependence and societies contrasting in individualism/collectivism. In the years following the work of Hoftsede (1980, 2001) and Triandis (1988, 1995), it has been suggested that the collectivism of some cultures such as Japan has been overstated and, in any event, is locally variable and has been subject to change (Matsumoto, 1999, 2002; Takano and Sogon, 2008; Yamawaki, 2012). Such a point of view might be interpreted as rendering collectivism/individualism (and the interdependent/individual self construct) less useful as explanations for east/west differences in unrealistic optimism than formerly thought.…”
Section: Resultsmentioning
confidence: 99%
“…A key focus has been the relationship of self-enhancement and self-effacement to selves contrasted in terms independence/interdependence and societies contrasting in individualism/collectivism. In the years following the work of Hoftsede (1980, 2001) and Triandis (1988, 1995), it has been suggested that the collectivism of some cultures such as Japan has been overstated and, in any event, is locally variable and has been subject to change (Matsumoto, 1999, 2002; Takano and Sogon, 2008; Yamawaki, 2012). Such a point of view might be interpreted as rendering collectivism/individualism (and the interdependent/individual self construct) less useful as explanations for east/west differences in unrealistic optimism than formerly thought.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the Descriptive norms represent a behavior in line with others rather than the value of cancer screening, which could be caused by the influences of collectivism in Japanese culture. Caution is necessary before interpreting cultural differences because there have been researchers that deny the influence of cultural differences such as collectivism and individualism on human behavior (Takano & Sogon, 2009). However, we consider that future studies are necessary, which bear in mind these cultural differences and Social norms.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, knowledge of CRC screening is perceived to be a precognition in an effort to effectively intervene in behavioral change (Kiviniemi et al, 2011). The knowledge of CRC and CRC screening has been identified as a predictor of CRC screening (Ng et al, 2007;Sieverding et al, 2010;Takano & Sogon, 2009). However, an association between knowledge and behavior has yet to be identified (Liang et al, 2006;Ng et al, 2007;Subramanian et al, 2004;Weinberg et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although this method allowed us to collect more than 400 words from adolescents, if we took a different approach, such as an interview method, we could assess more in-depth images of personal growth that the adolescents may hold. Second, individualistic and collectivist cultures and the impact of these cultures on the results was discussed at length, yet, only adolescents in the United States and Japan were included, and a recent study suggested that Japanese are not necessarily more collectivistic than those in the United States (Takano & Sogon, 2008). This limits the generalizability of our findings specifically to Japanese and United States adolescents.…”
Section: Discussionmentioning
confidence: 99%